2017
DOI: 10.1097/j.pain.0000000000001038
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral white matter structure is disrupted in Gulf War Veterans with chronic musculoskeletal pain

Abstract: Chronic musculoskeletal pain (CMP) affects ∼25% of the 700,000 Veterans deployed during the Persian Gulf War (1990-1991). The cause of their pain is unknown, and there are no efficacious treatments. A small body of literature suggests that brain abnormalities exist in Gulf War Veterans (GVs), yet relationships between brain abnormalities and disease symptoms remain largely unexplored. Our purpose was to compare white matter (WM) integrity between GVCMP and matched, healthy Veteran controls (GVCO) and investiga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
26
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 62 publications
1
26
0
Order By: Relevance
“…Much of the DTI and FA studies have been focusing on examining differences in white matter microstructure in chronic pain vs. non-pain controls, and correlating FA with pain levels (see a recent review paper [71]). Based on TBSS, pain-related FA reductions have been detected in multiple white matter tracts along diffuse 'white matter skeletons', including the internal and external/extreme capsules, corpus callosum, cingulum, thalamic radiation, and brainstem white matter, primary somatosensory and motor cortices, orbitofrontal cortex [72,73], rostral anterior cingulate, and dorsal lateral prefrontal cortex [74]. TBSS and most voxel-based analytic approaches, however, are known to be highly sensitive to registration errors and may produce false positive findings [75].…”
Section: Quantitative Brainstem Tractography and Painmentioning
confidence: 99%
“…Much of the DTI and FA studies have been focusing on examining differences in white matter microstructure in chronic pain vs. non-pain controls, and correlating FA with pain levels (see a recent review paper [71]). Based on TBSS, pain-related FA reductions have been detected in multiple white matter tracts along diffuse 'white matter skeletons', including the internal and external/extreme capsules, corpus callosum, cingulum, thalamic radiation, and brainstem white matter, primary somatosensory and motor cortices, orbitofrontal cortex [72,73], rostral anterior cingulate, and dorsal lateral prefrontal cortex [74]. TBSS and most voxel-based analytic approaches, however, are known to be highly sensitive to registration errors and may produce false positive findings [75].…”
Section: Quantitative Brainstem Tractography and Painmentioning
confidence: 99%
“…Based on our findings we predict that GW veterans would have decreased white matter integrity varying by brain region. These predictions are supported by the brain imaging studies of GW veterans (Bierer et al, ; Rayhan et al, ; Van Riper et al, ). The published neuroimaging data reflect both increased and decreased myelin integrity depending on the myelin track analyzed and methodological differences in measurement.…”
Section: Discussionmentioning
confidence: 76%
“…Importantly, an equal number of studies have identified decreased myelin integrity depending on the brain region. It has been shown in veterans with GWI and chronic pain that there is a lower white matter integrity across multiple brain regions including the frontal gyrus, corpus callosum, and precentral gyrus (Van Riper et al, ). GW veterans with PTSD also display significantly reduced mean diffusivity in the right, but not left cingulum (Bierer et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Much of the DTI and FA studies have been focusing on examining differences in white matter microstructure in chronic pain vs. non-pain controls, and correlating FA with pain levels (see a recent review paper [40]). Based on TBSS, pain-related FA reductions have been detected in multiple white matter tracts along diffuse ‘white matter skeletons’, including the internal and external/extreme capsules, corpus callosum, cingulum, thalamic radiation, and brainstem white matter, primary somatosensory and motor cortices, orbitofrontal cortex [41,42], rostral anterior cingulate, and dorsal lateral prefrontal cortex [43]. TBSS and most voxel-based analytic approaches, however, are known to be highly sensitive to registration errors and may produce false positive findings [44].…”
Section: Discussionmentioning
confidence: 99%